Evaluation of sheep and their lamb’s productive performance with or without strategic supplementation under grazing conditions - Herrera-Corredor, Camelia Alejandra; Salazar-Murillo, Erika Alejandra; Sánchez-Hernández, Miguel Ángel; Rosales-Nieto, César Augusto; Zaragoza-Bastida, Adrian; Rivas-Jacobo, Marco Antonio (Ecosistemas y Recursos Agropecuarios, 2021)
The productive performance of grazing ewes with and without supplementation at critical times and the performance of lambs were evaluated  at the Faculty of Agronomy and Veterinary Medicine of the Autonomous University of San Luis Potosí, at 22.23 ° LN and at 100.85 ° LO, at 1,835 m.a.s.l. In mild dry weather. 24 sheep females of the Rambouillet breed were used, with an average weight of 55 kg in irrigated fescue grasslands. Three treatments were used, 1) only grazing, 2) 300 gr / day of supplement (stubble + 10% chickpea + 5% zeolite) per sheep and  3) 400 gr / day of supplement (stubble + 20% chickpea + 5% zeolite) per sheep. The ewes were measured the Weight at mating (WM), at parturition (WP) and at weaning (WW), Body condition at mating (BCM), parturition (BCP) and weaning (BCW; Lambs were measured at birth weight (BWL) and weaning (WWL), as well as Female Weight Gain (FWG), and Lamb Daily Weight Gain (LDWG). A completely random statistical model was used. Weight, weight gain and body condition of females was favored by strategic supplementation by providing greater nutrients in the breeding stages, last third of gestation and lactation, which was reflected in higher weights of the lambs at birth and weaning.